THE HISTORICAL DEVELOPMENT OF BEKTASHISM IN KOSOVO - Durguti, Abdylkader (Ankara Haci Bayram Veli University, 2025)
In the 17th century, Kosovo was a region under the rule of the Ottoman Empire. Different religious movements have emerged in this region since early times. One of these is Bektashism. The interest shown by Albanians in Bektashism led to a notable increase in the number of Bektashi lodges, particularly in the regions of Albania and Kosovo. By the late 19th century, with the rise of nationalist movements in the Balkans, Bektashism had become one of the key religious and cultural elements supporting Albanian nationalism. During this period, the order was perceived not only as a religious structure but also as a symbolic component of Albanian national identity. By the 20th century, Bektashism, originally rooted in the Turkish Sufi tradition with Turkish as its liturgical language, underwent significant transformation under the influence of Albanian nationalism. Its rituals were translated into Albanian, and it developed a distinct structure referred to as “Albanian Bektashism.” The Bektashi presence in Kosovo was institutionalized later than in Albania and its influence remained more limited. Nevertheless, it is known that the first Bektashi lodge in Kosovo was established in the 17th century. Today, the majority of academic research on Bektashism focuses primarily on Albania, and the Bektashi structures in Kosovo are generally addressed within this framework. The background to this approach was the fact that approximately 93% of Kosovo’s population is of Albanian origin and has strong socio-cultural ties with Albania. The aim of this study is to examine the historical development of Bektashism within the borders of Kosovo, its institutionalization and expansion processes, its structural and cultural transformations and its relations with other Sufi structures. In particular, the wars and conflicts driven by Serbian and Albanian nationalisms in the post-Ottoman era significantly impacted the Bektashi lodges. Since Bektashism had become closely associated with Albanian nationalism, it was seen by the Serbs not merely as a religious institution but as a symbol of national identity, and therefore targeted during times of conflict. This situation shows that Bektashism has become an ideology and political meaning beyond being a religious structure in Kosovo. In this study, a multidimensional analytical approach is adopted by utilizing sources in Turkish and English, as well as Albanian literature and up-to-date data. © Creative Commons Attribution-NonCommercial 4.0 International (CC BY-NC 4.0)
TARİHSEL SÜREÇTE KOSOVA’DA BEKTAŞİLİĞİN GELİŞİMİ
Keywords: Bektashism; Gjakova; Haji Adem Veçhi Baba; Kosovo; Prizren